2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26118
|View full text |Cite
|
Sign up to set email alerts
|

The Design Projects for the Simulation-Based Design Course

Abstract: Ali R. Moazed is a Professor in the Mechanical Engineering and Technology department at Wentworth Institute of Technology. In addition to twenty five years of industrial and consulting experience, he has taught mechanical engineering courses full or part-time prior to joining Wentworth in 2001. At Wentworth, he teaches design related courses in the solid mechanics area. He believes in teaching from the perspective of a practicing academician by bringing into the classroom topics related to the practice of engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Because FEA is a daily tool for design engineers in many industries [1.2] , mechanical engineering students must know how to use this tool during their education. Many engineering colleges have offered FEA-related courses to their engineering students [3,4,5,6,7] FEA commercial software is a version of solid mechanics and is expressed in the form of computer codes. It is commonly accepted that teaching pure theory and programming of the Finite Element Method (FEM) is for Master-Degree or Ph.D. candidate students and has not been taught for undergraduate engineering students.…”
Section: Introductionmentioning
confidence: 99%
“…Because FEA is a daily tool for design engineers in many industries [1.2] , mechanical engineering students must know how to use this tool during their education. Many engineering colleges have offered FEA-related courses to their engineering students [3,4,5,6,7] FEA commercial software is a version of solid mechanics and is expressed in the form of computer codes. It is commonly accepted that teaching pure theory and programming of the Finite Element Method (FEM) is for Master-Degree or Ph.D. candidate students and has not been taught for undergraduate engineering students.…”
Section: Introductionmentioning
confidence: 99%
“…We found that students were able to successfully follow the lectures and complete homework exercises relative to each of the main FEA skills such as restraints (loading and boundary conditions), meshing, meshing control and convergence. Unfortunately, we also found that most of the students had difficulty starting and carrying out the project to conduct a design evaluation of a real product [10] . Students did not have difficulty completing their homework assignment because each homework assignment was tailored to a specific FEA simulation skill.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of physical test demonstrations significantly improved students' understanding of fatigue theory [7,8,9] . Numerical simulation tools such as FEA (Finite Element Analysis) programs have become a wonderful and necessary tool for mechanical engineers and students [4,10,11,12] . FEA software was also frequently implemented in classrooms to conduct fatigue analysis [12~15] to help students visualizing fatigue analysis.…”
Section: Introductionmentioning
confidence: 99%